INFLUÊNCIA DO DESENVOLVIMENTO OVARIANO NA COMPOSIÇÃO CUTICULAR DA VESPA SOCIAL Polistes erythrocephalus - PIVA, Raul; TORRES, Viviana; ANTONIALLI-JUNIOR, William; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2017)
-